Avaliação da dor em repouso e durante atividades no pósoperatório de cirurgia cardíaca - Mello, Larissa Coelho de (Universidade Federal de São Carlos, 2013)
Some activities need to be stimulated in post-cardiac surgery, such as, mobilization, coughing, deep breathing exercises to avoid complications; however, these activities may be hinder by pain. An assessment of the pain at rest and during activities is needed in order to better deal with this occurrences. The main aim of this study was to assess the perception of pain after cardiac surgery via sternotomy during rest and in five selected activities (coughing, turning aside, deep breathing, sitting or standing up from a chair, and walking); the specific objectives were to identify the location and intensity of pain during rest and activities in postoperative cardiac surgery patients in the 1st, 2nd, 3rd and 6th days; to link the pain intensity with the activities and at rest, considering the postoperative days; to link the pain intensity with variables clinical-surgical; to characterize the pain through pain descriptors. A descriptive study of prospective cohort was carried out. A tool to collect socio-demographic and surgicalclinical data, a Multidimensional Scale for Pain Assessment (EMADOR) that consists of a numeric scale for pain intensity assessment, a body diagram to assess the pain location and an escalation of acute pain descriptors, were utilised. A total of 48 patients who undergone a cardiac surgery via sternotomy participated. All patients complained of pain during one of the activities in at least one of the postoperative days. The pain intensity at rest in the postoperative cardiac surgery was assessed to lessen with day in the following postoperative days. However, during the activities the pain level decreased from the 3rd, excepting for the coughing activity which decreased only in the 6th. The decreasing order of strength, when assessed the pain levels of all days, was: coughing, turning aside, deeply breathing and resting. The sternal region was the most frequently cited location of pain, followed by the epigastric region. The variables gender, age, type and duration of surgery showed weak correlation with the pain level. The keywords that best characterised the pain after cardiac surgery via sternotomy were: strong, intense, terrifying, deep and very severe. The high levels of pain may be contributing to a longer recovery period. The patients considered painful the multidimensionality of the phenomenon when using descriptors to characterize the perceived pain. The study allowed a better understanding of the aspects related to pain in the postoperative cardiac surgery.
Assessment of pain at rest and during activities in post-cardiac surgery
Keywords: Enfermagem; Coração - cirurgia; Dor; Pósoperatório; Avaliação da dor; Descritores; Cardiac surgery; Postoperative pain; Pain assessment; Descriptors; CIENCIAS DA SAUDE::ENFERMAGEM